2008
DOI: 10.1088/0004-6256/136/2/767
|View full text |Cite
|
Sign up to set email alerts
|

Accretion Disk in the Massive Binary Ry Scuti

Abstract: The UBVR light curves of the massive eclipsing binary RY Sct, obtained at the Maidanak Observatory from 1979 to 1992, have been re-analyzed in order to prove the hypothesis of the presence of an accretion disk in the system. This hypothesis is supported by a new spectroscopic study of Grundstrom et al., and by a specific light-curve shape exhibiting a slight asymmetry around the secondary minima and a small difference in the height of the successive maxima. The light-curve analysis was performed using a Roche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Among them, AF Gem, TU Her, AT Peg, TY Peg, Z Per, Y Psc, and X Tri are systems with low mass ratios, and consequently, they are strongly suspected to undergo a non-conservative MT era, accompanied by ML through the L3 point at a significant rate. Recently, light curves of several early-type systems with an accretion disk have been analyzed using the new improved code of Djurašević et al (2005Djurašević et al ( , 2008 for estimating the physical disk parameters. Their analysis has indicated the presence of a bright spot, a region on the disk edge opposite (and close) to the L3 point, through which matter is expected to escape from the system.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, AF Gem, TU Her, AT Peg, TY Peg, Z Per, Y Psc, and X Tri are systems with low mass ratios, and consequently, they are strongly suspected to undergo a non-conservative MT era, accompanied by ML through the L3 point at a significant rate. Recently, light curves of several early-type systems with an accretion disk have been analyzed using the new improved code of Djurašević et al (2005Djurašević et al ( , 2008 for estimating the physical disk parameters. Their analysis has indicated the presence of a bright spot, a region on the disk edge opposite (and close) to the L3 point, through which matter is expected to escape from the system.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we modelled the UBV light curves of the eclipsing binary star V448 Cygni (Kumsiashvili & Kochiashvili 2003) by using our improved code for the systems with accretion disc (Djurašević et al 2008). The light‐curve analysis shows that the model with an optically and geometrically thick accretion disc fits the observations very well.…”
Section: Discussionmentioning
confidence: 99%
“…The light‐curve analysis of V448 Cygni, performed by means of our modified code (Djurašević et al 2008), demonstrated that this light‐curve fitting code represents a useful tool for the analysis of light curves and for modelling of any conically shaped accretion disc and any brightness feature appearing on the disc lateral side. However, caution is required when interpreting the results, since the large number of free parameters makes the determination of the unique solution difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations